FRAIL IDEOLOGICAL CONTENT AND OPPOSITION POLITICAL PARTIES IN NIGERIA, 2014-2018 - IEREENU-NNABUGWU, Makodi; ONYEKWELU, Ginika; ONYEKWELU, Ebuka (Socialscientia: Journal of Social Sciences and Humanities, 2020)
This study interrogates the role and requisites of opposition political parties, particularly the place the ideological content of opposition political parties in the Nigerian political system. No doubt, by their nature political parties are presumed life-wires of democratic political systems. With reference to their frail ideological contents, how valid is the foregoing assertion in the context of opposition political parties in Nigeria? Data for the study were sourced through documentary sources and analysed through textual analytic technique. The study found that largely on account of the frailty of the ideological content of opposition political parties there is weak distinction between the cosmology and the mode of operation of both opposition and ruling parties in Nigeria. The general drive of both members of the ruling and opposition political parties is power grabbing at all costs even when grossly unprepared to deliver good governance. This largely explains why there are often massive defections that cut across ruling and opposing political parties. Against this backdrop, the study recommends that Nigerian political parties, especially those in opposition should rise to the occasion by generating and propagating clearly thought-out and ideologically adroit alternatives to the ruling political parties. In this way, the Nigerian political system will benefit from deep-seated ideological content and issue driven opposition.